Global Banking: Recent Developments and Insights from Research - Claessens, Stijn (Review of Finance, 2017)
Abstract Following recent crises, cross-border capital flows have declined considerably, and many advanced countries’ banks are retrenching. At the same time, banks from emerging and developing countries continue to expand abroad, and banking has become more regional. Research highlights that long-term debt flows are less volatile and that foreign banks with larger presence, more domestic funding, and closer relationships provide more finance and share risks better. While ongoing changes in global banking influence its overall benefits, the crises also revealed the need for a consistent framework for supervising and resolving globally active banks, with the European Banking Union an important model.